PERANCANGAN PENGUKURAN KINERJA KARYAWAN DI MONUMEN KAPAL SELAM SURABAYA - Jessi Suhartini Gondowijoyo; Bonnie Soeherman (Perpustakaan Universitas Surabaya, 2018)
It can’t be argued that human resources are the most important in a organization. This is because his/her role as the executor of human resources even though human resources also has innate traits difficult to control. Therefore, every organization needs a control in order to create alignment goals between employees and organization.The results of the evaluation conducted in this study indicate that there are several issues related to the performance of employees who must be repaired immediately. From the results of this study, the researcher finds some existing problems related to employee performance, analyzes what causes the problem, informs the implicationsarising from the problem, and provide recommendations on the design of employee performance measurement to facilitate the organization in achieving the objectives. The main problem that occurred in the Monument Submarine related to the problem of control